Methodical aspects of production and stimulation of creativity of preschool children - Havryliuk, Svitlana M. ,; Kushnir, Valentyna M.; Golub, Nadiia P.; Golub, Volodymyr M.; Avramenko, Oksana O. (International Journal of Psychosocial Rehabilitation, 2020)
In connection with the modernization of the content of modern preschool education, the introduction of a new paradigm of education, which aims at shaping the person of modern times, developing their creative capabilities and creativity, the issue of the development of creative personality becomes greatly significant. Considering the importance of the preschool period for actualization of the creative potential of the individual, the preschool age is characterized as a sensitive period in the development of children's creativity. The article analyses the theoretical and methodological aspects of the development of preschool children's creativity on the basis of hild-centrism, co-creation, and cooperation. Definitions of such concepts as "creativity" and "children's creativity"are generalized and formulated. Contents of the concept of "creativity of children of preschool age" are considered by the authors of the article as the creative position of the child, its activity, imagination, invention, which is manifested in creative pursuit upon creating new ideas, artistic, creative images, communication, cognition of something new, unusual in the process of creative productive activity: playing, drawing, singing, dancing, communicative interaction and more. The pedagogical conditions for the development of creativity of preschool children are substantiated: creation of sensory and development environment in preschool educational institution and in the family, constructive interaction of teachers of preschool educational institutions with families of pupils, creative personality of the educator. The authors of the article emphasize the necessity of play activities, in particular, creative games in the development of imagination, thinking, fantasy children of preschool age.